Eastern valleys between the Jebab River and the Kala Badra morphological study - كريم حمد الساعد ي أ.م. د . حسين (lark, 2019)
The importance of studying these areas comes from the fact that the river networks are important water resources for the population and for the development projects represented in building small dams to collect water for agricultural purposes to reduce the risk of torrents in the rainy season, as many human activities and activities are concentrated in river basins and areas of discharge. The course of the rivers is affected by many external factors such as the amount of rain, as well as the factors within the river channel, such as the type of rocks for the river’s stream, the morphology of the river channel, the amount of load and the speed of flow. The terrain is one of the factors affecting river drainage in terms of increasing or decreasing speed of flowing water temporally and spatially along the course of rivers The morphometric analysis of the study area was used, and accordingly, it was classified on the basis of the water dividing line according to the satellite imagery and taken from the space sensors into seven valleys whose height ranges between Iraqi and Iranian lands 11-187 A.D. The study area areas were also classified according to the satellite data (NROL-65) Also the satellites, the American GIS program and the Google Erth program. The goal of geomorphological and morphometric analysis is to know the relationship between the Earth’s surface forms and drainage basins and their waterways, as the study of water basins using geographical information systems represents as it contributes to the interpretation of terrestrial forms and water drainage, as well as its relationship to the Earth’s surface through analysis of data, space visuals, images and digital properties such as a model Digital height (DEM) and digital images (y.x.z) from which contour lines, direction of slope, and water network can be known.